PERSPEKTIF SISTEM INFORMASI AKUNTANSI SEBAGAI STRATEGI KOMPETITIF USAHA KECIL - Agnes Dwita Susilawati; Fahmi Firmansyah; Budi Susetyo; Yuniarti Herwinari; Sri Mudiati (Komitmen: Jurnal Ilmiah Manajemen, 2023)
Small and medium enterprises (SMEs) are the largest contributor to state revenues in Indonesia. However, along with the development of information technology, SMEs are forced to follow the use of information technology-based accounting information systems as a competitive strategy. The limited quality of SME human resources is the main factor hindering the use of accounting information systems to improve performance and competitive strategies to compete with other SMEs. Research journal research methodology is the choice of researchers to reduce the concept of novelty as an alternative strategy for improving the performance of SMEs. The concept of the novelty model is Subjective Planning Innovation, which is a plan that is owned, designed, stored, used and updated (innovation) that uses an indirect accounting recording system by SME entrepreneurs based on previous work experience (subjective). Furthermore, the model concept, dimensions and limitations of the study are explained in detail in this study.